Numerical Simulation of undular bore evolution with chezy friction, 2015 - Tiong, W. K.; Chiew, K. L.; Tay, K. G.; Ong, C. T. (2015)
This paper studies and simulates numerically the evolution of undular bore under the effect of damping in the framework of the perturbed extended Korteweg-de Vries equation. Here, we consider Chezy frictional term to be the damping term in the perturbed extended Korteweg-de Vries equation. Numerical simulations show that under the influence of the friction, the undular bore with thick leading wave will transform into KdV-like solitary wave as the leading wave of the undular bore. The amplitude of the "thick" leading wave will remain the same for some time even though there is dissipation effect.